Hubungan Pengetahuan Ibu Balita Terhadap Perilaku Pencegahan Diare di Puskesmas Botania Kota Batam - Putra Hendra; Syaiful Batubara; Dianty Auliannisa (Universitas Batam, 2022)
Background: At the Botania Public Health Center in 2019 there were 2,173 diarrhea sufferers, while in 2020 there were 3,009 cases of diarrhea in all age groups, this shows an increase in diarrhea sufferers from 2019, and for children with diarrhea in toddlers in 2020 there were 1,879 cases or 62% of all age groups. The high number of cases of diarrhea in children under five in the working area of the Botania Public Health Center in Batam City in 2020 compared to other Public Health Center in the Batam City area. Methods: This research is a quantitative research using research design with analytical descriptive method and cross sectional approach. This research was conducted at the Botania Public Health Center in Batam City in December 2021. The sample in this study was 54 respondents. The sampling technique is Accidental Sampling. Data analysis used univariate analysis and bivariate analysis with Chi Square test. Results: The results of statistical tests using the Chisquare test obtained a value of p = 0.027 (p <0.05) which means H0 is rejected and Ha is accepted, so it shows that there is a significant relationship between the knowledge of mothers of children under five about diarrhea and diarrhea prevention behavior at the Botania Public Health Center City Batam. Conclusion:Based on the results of this study, it was found that good mother's knowledge had an effect on good diarrhea prevention behavior as well.